2016
DOI: 10.1007/s11069-016-2612-6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale debris flow vulnerability assessment and direct loss estimation of buildings in the Eastern Italian Alps

Abstract: Vulnerability assessment, as a component of the consequence analysis, represents a fundamental stage in the risk assessment process because it relates the hazard intensity to the characteristics of the built environment that make it susceptible to damage and loss. The objective of this work is to develop a quantitative methodology for vulnerability and loss assessment of buildings exposed to debris flows and apply it to a study area in NE Italy at local and regional scale. Using existing conceptual models of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 48 publications
0
23
0
3
Order By: Relevance
“…The use of vulnerability parameters or lethality values as a function of process-specific intensities is often based on incomplete or insufficient statistical data resulting from missing event documentation (Fuchs et al, 2013). As discussed in Kappes et al (2012a), Papathoma-Köhle et al (2011, 2017 and Ciurean et al (2017) with respect to mountain hazards, potential sources of uncertainty in vulnerability assessment are independent of the applied assessment method. The amplitude in data is considerably high in continuous vulnerability curves or functions, but also in discrete (minimum and maximum) vulnerability values referred to as matrices (coefficients), and in indicator-/index-based methods used to calculate the cumulative probability of loss.…”
Section: Uncertainties Within Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of vulnerability parameters or lethality values as a function of process-specific intensities is often based on incomplete or insufficient statistical data resulting from missing event documentation (Fuchs et al, 2013). As discussed in Kappes et al (2012a), Papathoma-Köhle et al (2011, 2017 and Ciurean et al (2017) with respect to mountain hazards, potential sources of uncertainty in vulnerability assessment are independent of the applied assessment method. The amplitude in data is considerably high in continuous vulnerability curves or functions, but also in discrete (minimum and maximum) vulnerability values referred to as matrices (coefficients), and in indicator-/index-based methods used to calculate the cumulative probability of loss.…”
Section: Uncertainties Within Risk Assessmentmentioning
confidence: 99%
“…The amplitude in data is considerably high in continuous vulnerability curves or functions, but also in discrete (minimum and maximum) vulnerability values referred to as matrices (coefficients), and in indicator-/index-based methods used to calculate the cumulative probability of loss. Associated with the uncertainty in vulnerability matrices, Ciurean et al (2017) suggested a fully probabilistic simulation in order to quantify the propagation of errors between the different stages of analysis by substituting the range of minimum-maximum values with a probability distribution for each variable in the model. listed potential sources of uncertainties in risk assessment models and classified uncertainties into aleatory and epistemic uncertainties.…”
Section: Uncertainties Within Risk Assessmentmentioning
confidence: 99%
“…In this study, vulnerability was expressed as a comprehensive index estimated through principal component analysis (PCA) and set as a range from 1 to 100. the construction of an evaluation index system is a commonly used method to integrate different categories of affected elements, to synthesize the vulnerability index by statistical methods or other mathematical methods, and to represent the relative degree of vulnerability of the assessment unit [54][55][56][57]. Considering the availability and consistency of socio-economic data in debris flow watersheds which normally correspond to the township scale, 11 variables (Table 1) were included and were mostly inferred from previous representative studies [58][59][60]. The procedures of PCA are described by Jolliffe [61].…”
Section: Vulnerabilitymentioning
confidence: 99%
“…Slow-moving landslides are observed worldwide in many countries, e.g. Italy (Cascini et al, 2008;Antronico et al, 2015;Uzielli et al, 2015a;Borrelli et al, 2018;Ferlisi et al, 2019), Canada (Clifton et al, 1986;Brooker and Peck, 1993;Moore et al, 2006;Barlow, 2000), China (Chen et al, 2016;Zhang et al, 2018;Dong et al, 2018;Wang et al, 2018), the USA (Esser, 2000), and Australia (Jworchan et al, 2008). Fell et al (2008) suggested the estimation of the physical vulnerability of elements at risk for various landslide types.…”
Section: Introductionmentioning
confidence: 99%